2018
DOI: 10.1039/c8fd00010g
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure prediction of flexible pharmaceutical-like molecules: density functional tight-binding as an intermediate optimisation method and for free energy estimation

Abstract: Successful methodologies for theoretical crystal structure prediction (CSP) on flexible pharmaceutical-like organic molecules explore the lattice energy surface to find a set of plausible crystal structures. The initial search stages of CSP studies use relatively simple lattice energy approximations as hundreds of thousands of minima have to be considered. These generated crystal structures often have poor molecular geometries, as well as inaccurate lattice energy rankings, and performing reasonably accurate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 97 publications
(142 reference statements)
0
37
0
Order By: Relevance
“…The resulting unique structures were then optimised with DFTB3-D3 31 to relax atomic positions and remove the possible unfeasible geometries derived from the use of rigid fragments of the molecule. The accurate evaluation of the lattice energies were performed with a single step DMACRYS 32 calculation, using distributed multipoles obtained from the PBE0/aug-cc-pVDZ charge density with GDMA2.2 33 and the repulsion-dispersion potential described in the previous paragraph.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting unique structures were then optimised with DFTB3-D3 31 to relax atomic positions and remove the possible unfeasible geometries derived from the use of rigid fragments of the molecule. The accurate evaluation of the lattice energies were performed with a single step DMACRYS 32 calculation, using distributed multipoles obtained from the PBE0/aug-cc-pVDZ charge density with GDMA2.2 33 and the repulsion-dispersion potential described in the previous paragraph.…”
Section: Methodsmentioning
confidence: 99%
“…Some discrepancies between the predicted and experimental geometries occurred for the ligand: Macromolecule complexes in unusual conformational space, rare rotamer examples, uncertain bond types, and some other cases, nevertheless, theoretical configuration space represents well experimental data [265,266] or configurations obtained by the Molecular Operating Environment's Low Mode Molecular Dynamics module [267]. It was demonstrated that the CSD-Conformer Generator combined with ab initio [268] or DFTB3-D3 [269] calculations can be used for crystal structure prediction of some flexible pharmaceuticals. Such combination reproduced well the molecular geometry and crystal parameters, although did not provide sufficiently accurate energy ranking.…”
Section: Csd-conformer Generatormentioning
confidence: 98%
“…In this review, we put aside many questions related to high-pressure polymorphism of organic compounds: kinetic barriers for phase transitions which play an important role [102][103][104][105], temperature corrections for DFT methods [106][107][108], prediction of new phases (which in future can significantly decrease amount of experimental work) [109][110][111], etc. Nevertheless, as it is shown above, current computational methods can bring out many more answers than pure experimental results.…”
Section: Combined Techniquesmentioning
confidence: 99%